Microwave absorber based on biocomposites derived from agricultural wastes with reinforcement of poly lactic acid - Baharudin, Elfarizanis (2021)
The development of new microwave absorber (MA) materials has been motivated by an increasing ecological and environmental consciousness. Biocomposites is natural fibre-reinforced polymers has low density and biodegradable nature obtain from natural fibers which are cheap, continuous supply, easy and safe handling. The idea of this research is to develop a MA from biocomposite derived from oil palm fronds (OPF), empty fruit bunch (EFB), pineapple leaf fiber (PALF) and strengthened with poly-lactic acid (PLA). The fibers samples are prepared in 0.3 mm particle size, meanwhile the polymer and biocomposites are in ring shaped forms using mix and blend process and injection moulding. Their dielectric constant, (ɛ') and loss tangent, (tan ) are extracted using open ended coaxial probe and S-parameter Reflection measurements. OPF, EFB and PALF show ’with 1.92, 1.88 and 2.04 respectively and tan  with 0.105, 0.096 and 0.102 respectively. PLA ’ and tan  is about 1.99  0.25 and 0.044  0.02 respectively in the X band. Each type of biocomposite mixture of fiber and PLA composition (wt%) namely OPFPLA, EFBPLA, and PALFPLA prepared in 10 wt%, 20 wt%, 30 wt%, 40 wt% and 50 wt% fiber loadings. The optimum ’ and tan  for each biocomposite is 2.718 and 0.165 at fo = 8.6 GHz for OPFPLA5050 with 50 wt% OPF and 50 wt% PLA, meanwhile 2.079 and 0.168 at fo = 8.8 GHz for EFBPLA5050 with 10 wt% EFB and 90 wt% PLA and 2.23 and 0.09 at fo = 8.4 GHz for PALFPLA with 50 wt% PALF and 50 wt% PLA. The MA performance is observe from CST simulation, where S11 and S21 parameters are the key factors of MA absorption rates (AR), fractional bandwidth (FBW) and its thickness, d is used to determine the new formulation of figure of merit (FOM) for the percentage of wave absorption per unit milimeter (mm). OPFPLA5050 MA with d = 9 mm resonates at 8.6 GHz show the optimum performance with AR of 40.9%, FBW of 31.2% and the FOM is 4.5% per unit mm using normal incident in TE and TM polarization. When incident wave transmitted in variation angles of , the AR and FBW increase as  increases until 45o in TE and TM polarization. Then, OPFPLA5050 MA is fabricated using 30 x 30 x 1 cm3 mould and hot press machine. It is measured using free space and bistatic reflection methods. The results shows OPFPLA5050 MA with d = 10 mm resonates at 8.17 GHz with AR is 35.9%, FBW is 7.42 % and FOM is 3.6% per unit mm. Due to fabrication error, the MA thickness is different form the simulation although their plots show same trends except for the shifted resonant frequency. A fine-tune simulation shows that the fabricated MA consider to have ’ = 2.46 and tan  = 0.12 and frequency at 8.17 GHz where the corresponding AR is 32%, FBW is 26.8% and FOM is 3.2% per unit mm which is close to the fabricated results. Then, a similar trend observed with the simulations when  varies from 0o in 45o in TE and TM polarization. Therefore, these findings on natural fiber reinforced PLA biocomposites have significant implications in the application of microwave absorber. The unique composition between oil palm frond fibers and PLA demonstrates promising wave absorption for further exploration as alternative material in future research.